Ambidextrous governance of IT-enabled services: A pragmatic approach. Issue 4 (December 2020) - Singh, Rajendra; Baird, Aaron; Mathiassen, Lars
Abstract: Organizations must continuously allocate and reallocate limited resources, including IT resources, to competing innovation and operational concerns. While the ambidexterity literature provides some guidance regarding resource allocation approaches, studies typically assume that such tensions can be balanced without taking contextual and trade-off issues into account. Further, many studies examine ambidexterity approaches individually without considering how different approaches may be combined. To address these shortcomings, we pragmatically examine how a U.S. health delivery organization responded to technological, regulatory, and demand changes over a 15-year period and the effects of its actions. To manage the consequential tensions between innovation and operation of its IT-enabled services, we retrospectively observe that the organization applied a portfolio of sequential, structural, and contextual ambidexterity approaches. As a contribution to the IT governance and health IT literatures, the study offers theoretical and practical knowledge on how organizations can pragmatically apply ambidexterity in highly dynamic contexts to mindfully orchestrate and coordinate between innovation and operation of their IT-enabled services. Highlights: · Highlight challenges in managing competing innovation and operational tensions in delivering IT-enabled services in dynamic environments The competing concerns cannot simply be "balanced" without taking contextual and trade-off issues into account Examine how a health delivery organization addressed the competing concerns through sequential, structural, and contextual ambidexterity Demonstrate how organizations can pragmatically combine multiple ambidexterity approaches in highly dynamic contexts